DEVELOPMENT OF WARNING CRITERIA FOR LAHAR FLOW DISASTER IN GENDOL RIVER AREA OF MOUNT MERAPI - Ernowo Ary Fibriyantoro (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
The eruption of Mount Merapi in 2010 leads to the lahar flow disaster in the region of the mountain slopes. Due to the impact caused by the lahar flow, it is important to develop warning criteria for lahar flow disaster with a simple method corresponding to the limitation of existing data and parameters. One of the methods is by analyzing rainfall data to predict the occurrence of lahar flow in Gendol River. It applies the setting of standard rainfall for warning and evacuation of sediment disasters based on Guidelines for the Development of Warning and Evacuation System against Sediment Disasters in Developing Countries, published by the Ministry of Land, Infrastructure, and Transport (MLIT) Infrastructure Development Institute - Japan, 2004. This study analyzed the critical line (CL) which can be used to predict the occurrence of lahar flow based on the rain characteristics namely working rainfall and rainfall intensity. Furthermore, it can be established by warning line (WL) and the evacuation line (EL) as a basis for determining the standard rainfall for warning (R1) and standard rainfall for evacuation (R2). The value of R1 obtained ± 6 mm and R2 ± 29 mm. The value of R1 and R2 are strongly influenced by the availability of rainfall data and occurrence of lahar flow. The results of this research were expected to be used as input for the warning criteria development of early warning system lahar flow disaster on the slopes of Mount Merapi, particularly in the area of Gendol River.